Goal Attainment Scaling: Its use with Pregnant and Single-Parent Teenagers in an Alternative Education Setting - Moyer, Linda S.; de Rosenroll, David A. (Canadian Journal of Counselling and Psychotherapy, 2011)
Goal Attainment Scaling (G.A.S.) was initiated in the 1960's as an evaluation tool to measure success in Mental Health Programs. This article describes a modification of G.A.S. used within a day program for pregnant and parent teenagers. As a program assessment tool, G.A.S. provides the users with immediate, understandable feedback: what worked and what didn't work. As a counselling intervention, G.A.S. allows helping professionals to form a working relationship with their clients in a relatively short time span, to align their client/program expectations and to provide productive counselling on client-determined goals.